2017
DOI: 10.1159/000455934
|View full text |Cite
|
Sign up to set email alerts
|

WNT5A Correlates with Clinicopathological Characteristics in Gastric Cancer: a Meta-Analysis

Abstract: Background/Aims: Gastric cancer (GC), the third-leading cause of cancer death in the world, is typically diagnosed only in its advanced stages. WNT signaling has been associated with clinicopathological characteristics in diverse cancer types. But the systematic analysis of WNT5A, a member in the signaling, has not been inspected. Thus, our study used a meta-analysis to statistically associate WNT5A expression with GC clinicopathological characteristics. Methods: For a systematic literature review of GC in com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 25 publications
(29 reference statements)
1
13
0
Order By: Relevance
“…Inhibition of WNT5A by its antagonist, Box5, cancelled the CAFs' enhancing effects on cancer cell growth and migration. The prognostic impact of WNT5A expression was observed in the database, in line with previous studies 16 47…”
Section: Discussionsupporting
confidence: 90%
“…Inhibition of WNT5A by its antagonist, Box5, cancelled the CAFs' enhancing effects on cancer cell growth and migration. The prognostic impact of WNT5A expression was observed in the database, in line with previous studies 16 47…”
Section: Discussionsupporting
confidence: 90%
“…Gastric cancer has become the 3rd leading cause for cancer death in the world ( 1 ), and ranks 1st in all malignant tumors in China. Most of the gastric cancer patients have been diagnosed as the adenocarcinoma type.…”
Section: Introductionmentioning
confidence: 99%
“…Most of the gastric cancer patients have been diagnosed as the adenocarcinoma type. Currently, pathogenesis of gastric cancer remains unknown due to the heterogeneity in histological and pathological features of gastric cancer, and the diagnostic rate in an early stage is relatively low; nowadays, resection has been used as the preferred option for treatment of gastric adenocarcinoma without distant metastasis ( 1 , 2 ). According to the literature, it is reported that tumor diameter, regional lymphatic metastasis, vascular invasion, pTNM stage and surgical method are major factors affecting the prognosis of gastric cancer patients ( 3 – 5 ).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it remains possible that GC might proceed following not only Wnt5a overexpression but also impaired or unbalanced Wnt ligand availability. Finally, high Wnt5a expression is correlated with poor prognosis (Kurayoshi et al, 2006), and there is a statistically significant correlation between Wnt5a expression and several clinical parameters, such as lymph node metastasis and tumor depth (Nam et al, 2017).…”
Section: Wnt5a Expression In Gastric Cancermentioning
confidence: 97%